Introduction Des Organismes Génétiquement Modifiés(OGM) Dans L’agriculture En Côte d’Ivoire: Etat De Connaissance Et Souhaits Des Populations De Six (6) Localités Du Sud Du Pays - Boraud N’takpé Kama Maxime; Ake Séverin; Jacques Gasquez (European Scientific Journal, ESJ, 2016)
Transgenic plants with their huge potential as the high yields, resistance to diseases, insects and water stress seem to be a solution for Africa and could contribute to poverty reduction and the increase of agricultural production in this area of the world often face starvation. However GMOs dragging a trail of controversy and risk maligned with a series of impacts that concern the human health, environmental, social and economic. Is the dangerousness of transgenic plants a concern people of Ivory Coast? Investigations were carried out on 400 farmers and 1000 educated people in through a series of questions.